LncRNA SPANXA2-OT1 Participates in the Occurrence and Development of EMT in Calcium Oxalate Crystal-Induced Kidney Injury by Adsorbing miR-204 and Up-Regulating Smad5 - Hu, Haiyan; Zhang, Jie; Li, Yinhui; Ding, Jiarong; Chen, Wei; Guo, Zhiyong (Frontiers in Medicine, 2021)
Objective: To explore the regulatory mechanism of long non-coding RNAs (lncRNAs) in the occurrence and development of epithelial-mesenchymal transition (EMT) in calcium oxalate crystal-induced kidney injury. Materials and Methods: Gene core technique was used to screen differentially expressed lncRNAs and mRNAs in HK-2 cells before and after calcium oxalate monohydrate (COM) stimulation; differentially expressed mRNAs were then analyzed using GO and pathway analysis. The role of target lncRNA in EMT in renal tubular epithelial cells induced by COM was further investigated by applying a series of in vitro experiments. Results: Four differentially expressed lncRNAs (ABCA9-AS1, SPANXA2-OT1, RP11-955H22.1, and RP11-748C4.1) were up-regulated after 48 hours of COM stimulation compared to the control group, where up-regulated expression of lncRNA SPANXA2-OT1 was the most significant. Thus, lncRNA SPANXA2-OT1 was further examined. Interference lncRNA SPANXA2-OT1 reversed the down-regulation of E-cadherin and pan-ck, and up-regulated vimentin and α-SMA induced by COM stimulation. The application of miR204 inhibitor weakened the interference effect of interfering RNA on lncRNA SPANXA2-OT1 and promoted the occurrence of EMT. MiR204 simulator alleviated the overexpression effect of lncRNA SPANXA2-OT1 on COM-stimulated renal tubular epithelial cells and inhibited the occurrence of EMT in renal tubular epithelial cells. Moreover, a dual-luciferase reporter assay showed that miR-204 could bind to lncRNA SPANXA2-OT1 and Smad5, while lncRNA SPANXA2-OT1 could inhibit cell proliferation and promote cell apoptosis. Conclusion: The lncRNA SPANXA2-OT1 is involved in the occurrence and development of EMT in renal tubular epithelial cells induced by crystalline kidney injury by adsorbing miR-204 and up-regulating Smad5.